OKAPI, an Emotional Education and Classroom Climate Improvement Program Based on Cooperative Learning: Design, Implementation, and Evaluation - Maria-Jose Mira-Galvañ (MDPI AG, 2021)
A positive school climate can directly influence the relationships and social interactions among students while also contributing to the development of socio-emotional skills. Simultaneously, the school climate depends on these said skills. Despite this close relationship, emotional education and school climate improvement programmes have traditionally been studied separately. This study describes and evaluates the effectiveness of a new programme, OKAPI (Organisation, Cooperation, Positive Environment, Participation and Emotional Intelligence), for the development of socio-emotional skills and the improvement of classroom climate for primary school students using a cooperative learning methodology. The total sample comprised 86 students aged 9–11 years. A quasi-experimental design with pre-test and post-test measures with a control group was used. The results show that the program’s implementation is effective both for the improvement of the classroom climate and the acquisition of training in the field of emotional intelligence, as well as for the development of cooperative competences. Among the fundamental pillars of the OKAPI programme are its simplicity and transversality, so that teachers are responsible for its application and monitoring; thus, the programme becomes an agent of change in their educational practice.